An inordinate fondness for species with intermediate dispersal abilities. Issue 3 (3rd December 2019) - Ashby, Ben; Shaw, Allison K.; Kokko, Hanna
Abstract : J. B. S. Haldane is widely quoted to have quipped that the Creator, if one exists, has an inordinate fondness for beetles. Although Coleoptera may not be the most speciose order once Hymenopteran diversity is fully accounted for, as a whole the very clear differences in species diversity among taxa require an explanation. Here we use stochastic simulations to show that dispersal has eco‐evolutionary effects that predict taxa to become particularly species‐rich when dispersal is neither too low nor too high. Our model combines recent advances in understanding coexistence in niche space with previously verbally expressed ideas, where too low dispersal imposes biogeographic constraints that prevent a lineage from finding new areas to colonize (reducing opportunities for speciation), while too high dispersal impedes population divergence, leading to few but widely distributed species. We show that this logic holds for species richness and is robust to a variety of model assumptions, but peak diversification rate is instead predicted to increase with dispersal. Our work unifies findings of increasing and decreasing effects of dispersal rate on speciation, and explains why taxa with moderate dispersal abilities have the best prospects for high global species richness.